Application of different ventilator modes in patients with amyotrophic lateral sclerosis according to certain clinical situations: A Case Report - Park, Donghwi (Medicine (Baltimore), 2017)
RATIONALE: Amyotrophic lateral sclerosis (ALS) is a rapidly progressing neurodegenerative disease that involves limb, axial, bulbar, and respiratory muscles. Fatigue and weakness of the respiratory muscles eventually induce respiratory insufficiency, which is one of the main causes of death in patients with ALS. In ALS patients with respiratory insufficiency, application of a ventilator is indispensable. Although there are various modes of ventilation, these modes are classified roughly into volume-controlled ventilation (VCV) and pressure-controlled ventilation (PCV). There have been several reports that VCV is preferable to PCV in neuromuscular disorder patients, such as ALS patients, but there is still debate on which ventilator mode is better. PATIENT CONCERNS: Respiratory difficulty despite ventilator application. DIAGNOSIS: Three ALS patients with respiratory difficulty. INTERVENTION: Changing ventilator mode to improve symptoms of respiratory difficulty. OUTCOMES: Considering case 1 shows that the VCV mode may have an advantage in managing respiratory insufficiency of patients in situations where the inner diameter of the airway decreases because of increased sputum. In contrast, cases 2 and 3, it is shown that changing to the PCV mode may be one of the treatment options if not enough tidal volume can be supplied to resolve respiratory insufficiency because of an increase in leakage volume. LESSONS: Therefore, in this study, through considering several cases of ALS patients whose clinical symptoms were improved by changing ventilation mode, we tried to investigate the adequacy of each ventilation mode under certain clinical situations.